Measurement of Naval Ship Responses to Underwater Explosion Shock Loadings - Il-Kwon Park; Jong-Chul Kim; Chin-Woo An; Dae-Seung Cho (Shock and Vibration)
The shock-resistance capability of battle ships against a non-contact underwater explosion (UNDEX) is a very critical factor of survivability. In July 1987 and April 2000, we successfully conducted UNDEX shock tests for a coastal mine hunter (MHC) and a mine sweeper/hunter (MSH) of Republic of Korea Navy (ROKN), at the Chinhae bay, Korea. Test planning for conducting these shock tests included responsibilities, methods, and procedures. Test instruments were developed and tested on a drop shock machine to confirm availability in the actual shock tests with emphasis on shock resistance, remote control and reliability. All vital systems of the ships were confirmed to be capable of normal operational condition without significant damages during the explosion shot. By analyzing the test results, the tactical operational safety zone of the ships in underwater explosion environments was estimated. In this paper, we described the results of measurement of naval ship responses to underwater explosion shock loadings including test planning, sensor locations, data reduction, explosive devices, instrumentation and damage assessments of MSH.